Image rights payment: The taxation of resident sportspersons - Nzuza, Khulekani (Department of Finance and Tax, 2021)
The Sport industry has developed over the years and now can even form part of the entertainment industry. Sportspersons have become celebrities in their own right and their image rights are treated as commodities. The image rights of famous sportspersons are commercial products exploited by sports clubs and enterprises in promoting their brands through merchandising and endorsement deals. As a result, sportspersons earn income from the use of their image in promotional activities. The Income Tax Act No.58 of 1962 does not provide specific rules for the taxation of image rights payments and the Guide on the Taxation of Professional Sports Clubs and Players (the 2018 Guide) issued by the South African Revenue Service is not legally binding. Therefore, the income tax treatment of image rights payments is a subject of different interpretations and a cause for uncertainty. The capital or revenue nature (classification) of income from the sale or exploitation of image rights is unclear. The aim of this study was to determine the income tax classification of income derived by rugby, cricket and football players from the commercial exploitation of their image rights. The inquiry considered the regulations prescribed by the sport regulatory bodies, legislation, case law, literature and the section of the 2018 Guide which deals with image rights. A brief comparative study was also conducted to assess the tax position in the United Kingdom and United States of America. It was found that the South African law does not currently recognise an image right as a separable asset of an individual. Income emanates from the productive employment of an image right in lieu of its disposal therefore will form part of a sportspersons' gross income. The 2018 Guide also does not sufficiently address the income tax implications of the sale or exploitation of image rights. There is, therefore, a need for a legislative framework and a revised Guide to cater for the taxation of image rights payments.